A document-oriented LMS with integrated text classification for gender equality assessment - Cherednichenko, Olga; Tereshchenko, Glib; Kyrychenko, Iryna; Shanidze, Oleksandr; Vorzhevitina, Anzhelika I. (CEUR-W, 2025)
In response to the dynamic changes and crises affecting the education sector, this paper introduces a document-oriented Learning Management System (LMS) designed to integrate multiple independent components of E-Learning. By reviewing recent studies, trends, and competing standards in the LMS field, we propose an ontology for the document-oriented system and develop a framework for representing Learning and Practice Objects. This framework is tailored to support a multi-medium learning environment, reflecting the evolving technological needs in education. Approaches to integrate automatic text classification methods into a learning management system (LMS) to improve their functionality and effectiveness are proposed, particularly for gender equality assessment.
Keywords: automatic text classification; e-learning; gender inequality; learning analytics; LMS; system design